Coruption, Democracy And Women’s Political Representation : A Dynamic Panel Study Of Economic Growth In Developing Countries - Sukoco, Ibnu; Hasyim, Sirodjuzilam; Syafii, Muhammad (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study examines how three key institutional dimensions corruption, democracy and women’s political representation jointly shape economic growth in developing countries. Using annual panel data for 20 developing economies in Asia, Africa and Latin America over 2012–2024, real GDP growth is modelled as a function of corruption, democratic quality, women’s share of parliamentary seats, GDP per capita and foreign direct investment. A dynamic panel System GMM estimator is applied to address endogeneity, reverse causality and unobserved country-specific heterogeneity, with diagnostic tests indicating valid instruments and well-behaved error dynamics. The estimates point to strong growth persistence, implying that institutional shocks have both short-run and cumulative long-run effects on growth trajectories. Higher corruption is associated with lower economic growth, consistent with the view that corruption distorts resource allocation, discourages productive investment and undermines long-run performance. Democracy exerts a negative short-run effect on growth, reflecting transitional costs in partially consolidated democracies marked by political uncertainty and policy conflict. By contrast, women’s parliamentary representation has a positive and statistically significant association with growth, suggesting that more inclusive political institutions improve governance quality and support more growth-enhancing public policies. GDP per capita emerges as an important structural determinant of growth, whereas foreign direct investment does not exhibit a robust direct impact in the baseline specification. Overall, the findings underscore that anti-corruption reforms, carefully managed democratic transitions and stronger representation of women in politics are central to accelerating and sustaining inclusive economic growth in the Global South.